1993
DOI: 10.1007/bf00307733
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 in synovial fluid is closely associated with chronic synovitis in rheumatoid arthritis

Abstract: Interleukin-6 (IL-6) was detected at low levels in plasma [0.014 +/- 0.006 ng/ml (mean +/- SEM] and in high amounts in synovial fluid [SF; 2.6 +/- 2.2 ng/ml (mean +/- SEM)] of patients with rheumatoid arthritis. No correlation of IL-6 levels in plasma or SF with the ESR (n = 15) or with histological parameters of acute local synovitis (n = 10) was observed. In contrast, SF IL-6 was positively correlated with histological characteristics of chronic synovitis (n = 10; P < or = 0.01) and elevated plasma IgG conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0
10

Year Published

1994
1994
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(67 citation statements)
references
References 30 publications
1
56
0
10
Order By: Relevance
“…Excess production of IL-6 has been found in the synovial fluid and blood of RA patients and correlates with the disease activity and joint destruction [15,16]. IL-6 promotes synovitis by inducing neovascularisation via vascular endothelial growth factor (VEGF)-stimulated pannus proliferation, resulting in infiltration of inflammatory cells and synovial hyperplasia [17].…”
Section: The Role Of Interleukin-6 In the Pathogenesis Of Rheumatoid mentioning
confidence: 99%
“…Excess production of IL-6 has been found in the synovial fluid and blood of RA patients and correlates with the disease activity and joint destruction [15,16]. IL-6 promotes synovitis by inducing neovascularisation via vascular endothelial growth factor (VEGF)-stimulated pannus proliferation, resulting in infiltration of inflammatory cells and synovial hyperplasia [17].…”
Section: The Role Of Interleukin-6 In the Pathogenesis Of Rheumatoid mentioning
confidence: 99%
“…Thus, T-cell and neutrophil chemotaxis, a crucial process for leucocyte accumulation, is predominantly induced by interleukin (IL)-8 [6][7][8][9][10]. Other cytokines, such as IL-1, IL-6, tumour necrosis factor-␣ (TNF-␣), granulocyte and monocyte colony-stimulating factor (GM-CSF), transforming growth factor-␤ (TGF-␤) and IL-10, have also been detected in the RA joint [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. Overexpression of IL-1␣, IL-1␤, IL-6, TNF-␣, GM-CSF and epidermal growth factor (EGF) has been described in OA synovium [4,[24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…This concentration is a hundred times higher than we used. On the other hand, the applied concentration of IL-6 in our experiments was higher than in synovial fluid of patients with RA [50], and so biological activity was to be expected. We would argue that the concentration of IL-6 is not the limiting factor.…”
Section: Discussionmentioning
confidence: 51%
“…This could be due to missing costimulatory signals. Sack et al showed that IL-6 stimulates immunoglobulin production of isolated lymphocytes from RA-SM only when the cells are additionally incubated with phorbol myristate acetate (PMA) [50].…”
Section: Discussionmentioning
confidence: 99%